2018
DOI: 10.7717/peerj.4791
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of Onen’s Alternative Grading System combined with Doppler evaluation of ureteral jets as an alternative in the diagnosis of obstructive hydronephrosis in children

Abstract: IntroductionUreteropelvic junction obstruction (UPJO) is a common congenital anomaly leading to varying degrees of hydronephrosis (HN), ranging from no apparent effect on the renal function to atrophy. Evaluation of these children is based on Diuretic Renal Scintigraphy (DRS) and Ultrasonography (US). Recent studies have suggested that new parameters of conventional and color Doppler ultrasonography (CDUS) may be useful in discriminating which kidneys are obstructed. The present study aims to assess the diagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Considering parenchymal loss, SFU and UTD are the same, differing from the Onen grading system that stratifies it in cortical and medullary loss, which was found clearly more precise (1,21). Recent studies have shown that patients with Onen-3 had better renal function than Onen-4, proving that this difference is relevant to choosing this grading system for children (1,4,5,11,21). Bienias and Sikora have shown that 21/25 (84%) children with Onen grades 3 and 4 developed obstructive nephropathy with impaired relative function from 15 to 35% (44).…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Considering parenchymal loss, SFU and UTD are the same, differing from the Onen grading system that stratifies it in cortical and medullary loss, which was found clearly more precise (1,21). Recent studies have shown that patients with Onen-3 had better renal function than Onen-4, proving that this difference is relevant to choosing this grading system for children (1,4,5,11,21). Bienias and Sikora have shown that 21/25 (84%) children with Onen grades 3 and 4 developed obstructive nephropathy with impaired relative function from 15 to 35% (44).…”
Section: Discussionmentioning
confidence: 92%
“…Onen grading system has a sensitivity of 100%, specificity of 76%, and accuracy of 86.4% (21). In a recent study, all units that had Onen-1 and 2 were not obstructed and had renal function > 40% while Onen grade-4 had 100% specificity, meaning that it consistently predicts kidney damage due to obstruction when present (1,21). Therefore, renal scan is required for only Onen-3 patients; thus, renal scan could be avoided in more than two-thirds of cases (1,21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Postnatal ultrasound cut-off values for renal obstruction on DRS have been suggested to be 15–20 mm AD [27]. Onen’s alternative grading system, of grades 3 or 4 with no jets on a Doppler scan, increased sensitivity to 78.9% and accuracy to 92% in diagnosing obstruction [28]. Prospective study has shown that the parenchyma/hydronephrosis area ratio has been more accurate in predicting obstruction in comparison to SFU grade and AD, but requires specific software for calculations [29].…”
Section: Discussionmentioning
confidence: 99%